Efektivitas Penerapan Pertanian Presisi Berbasis Sensor Kelembapan Tanah Terhadap Efisiensi Penggunaan Air Dan Produktivitas Tanaman - Nurhayati Nurhayati (CV. SINAR HOWUHOWU, 2026)
Water-use efficiency is an important challenge in developing sustainable agricultural systems. Conventional irrigation practices based on fixed schedules or visual observations may result in excessive water use and may not correspond to the actual water requirements of crops. This study aimed to analyze the effectiveness of precision agriculture based on soil moisture sensors in improving water-use efficiency and crop productivity. A quantitative experimental approach was employed by comparing crops treated with sensor-based irrigation and those receiving conventional irrigation. Data were collected through measurements of soil moisture, water consumption, irrigation frequency, plant growth, and crop yield. The data were analyzed descriptively and inferentially to determine differences in water use and productivity between the two groups. The results indicated that the application of soil moisture sensors optimized irrigation by adjusting watering times according to the actual moisture conditions of the growing medium. The sensor-based system potentially reduced water consumption by approximately 20–30% compared with conventional irrigation, while crop growth and productivity were maintained or slightly improved. These findings demonstrate that soil moisture sensors can serve as an alternative technology for supporting more efficient irrigation management. Precision agriculture based on soil moisture sensing not only contributes to water conservation but also supports crop productivity and the sustainability of agricultural practices. Furthermore, this technology has the potential to be developed through integration with automated irrigation systems and the Internet of Things to improve the accuracy and efficiency of water management under various cultivation conditions.